Bank Concentration and Schumpeterian Growth: Theory and International Evidence - Diallo, Boubacar; Koch, Wilfried (The Review of Economics and Statistics, 2018)
This paper investigates the relationship between economic growth and bank concentration. We introduce imperfect competition within the banking system according to the Schumpeterian growth paradigm, and we theoretically and empirically show that the effects of bank concentration on economic growth depend on the proximity to the world technology frontier. The theory predicts that when a country reaches a sufficient level of financial development, bank concentration has a negative effect on development and growth and that this effect increases when the country approaches the frontier. However, for countries with credit constraints, growth depends on only financial intermediation.